Perceptual-motor development for children who show signs of attention deficit hyperactivity disorder (ADHD) - Rathbone, Ingha (Stellenbosch : University of Stellenbosch, 2009)
Thesis (M Sport Sc (Sport Science))--University of Stellenbosch, 2009.